1996
DOI: 10.1111/j.1558-5646.1996.tb04472.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Magnitude and Timing of Inbreeding Depression in Plants

Abstract: Estimates of inbreeding depression obtained from the literature were used to evaluate the association between inbreeding depression and the degree of self-fertilization in natural plant populations. Theoretical models predict that the magnitude of inbreeding depression will decrease with inbreeding as deleterious recessive alleles are expressed and purged through selection. If selection acts differentially among life history stages and deleterious effects are uncorrelated among stages, then the timing of inbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
793
16
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,044 publications
(889 citation statements)
references
References 90 publications
68
793
16
5
Order By: Relevance
“…A study with Vaccinium corymbosum (Ericaceae) found that heterozygosity increases due to the abortion of most self-fertilized seeds, a post-zygotic mechanism of high inbreeding depression (Krebs and Hancock, 1990). In a review, Husband and Schemske (1996) found general support for the theoretical prediction that, for outcrossing species, inbreeding depression tends to be expressed at early life stages. Although, there is no information on the mating system of A. murumuru and A. paramaca, close relatives, including A. mexicanum (Eguiarte et al, 1992) and A. aculeatum, are outcrossing (Ramos et al, 2011), and Oliveira NP, Oliveira MSP, Davide LC, Kalisz S (unpublished results) indicate that A. vulgare is outcrossing as well.…”
Section: Discussionmentioning
confidence: 93%
“…A study with Vaccinium corymbosum (Ericaceae) found that heterozygosity increases due to the abortion of most self-fertilized seeds, a post-zygotic mechanism of high inbreeding depression (Krebs and Hancock, 1990). In a review, Husband and Schemske (1996) found general support for the theoretical prediction that, for outcrossing species, inbreeding depression tends to be expressed at early life stages. Although, there is no information on the mating system of A. murumuru and A. paramaca, close relatives, including A. mexicanum (Eguiarte et al, 1992) and A. aculeatum, are outcrossing (Ramos et al, 2011), and Oliveira NP, Oliveira MSP, Davide LC, Kalisz S (unpublished results) indicate that A. vulgare is outcrossing as well.…”
Section: Discussionmentioning
confidence: 93%
“…Over generations, sel®ng may reduce the inbreeding depression because deleterious alleles should be purged (Husband and Schemske 1996). Ramsey and Vaughton (1996) also argue that pollination limitation raises the threshold of inbreeding depression below which selffertility evolves.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence, reduced inbreeding depression should be detectable. Current theory suggests that inbreeding depression in outcrossers is mainly expressed in early stages of the life cycle such as seed formation (Husband and Schemske 1996). I therefore wanted to know whether the seed set of self-pollinated compared with cross-pollinated¯owers of S. oppositifolia increases from low-to high-elevation populations, which would eventually lead to a shift towards self-pollination in the breeding system of S. oppositifolia.…”
Section: Introductionmentioning
confidence: 99%
“…The "trade-offs" approach to predicting the relationship between resistance and growth rate (Blossey and Notzöld 1995) does not consider effects of inbreeding (Charlesworth and Charlesworth 1987;Husband and Schemske 1996), which could act to reduce the average biomass of plants in introduced populations, especially if populations are established from a single introduction of a few founders. Inbreeding depression is likely to be an important factor affecting plant growth rates in introduced populations of smooth cordgrass since inbred (selfed) progeny have 30-90% slower growth rates than outbred progeny (Daehler 1996).…”
Section: Evidence For a Founder Effectmentioning
confidence: 99%